Struktur Komunitas Bulu Babi Di Perairan Pantai Kampung Baru Pulau Banda Kabupaten Maluku Tengah - Wakano, Deli; Chara Huwae, Laury Marcia (Biosel Biology Science and Education, 2020)
The waters of Kampung Baru Village are one of the waters in Banda Island, Central Maluku Regency, which has an abundance of marine life. The substrate conditions in these waters are rocky, rocky and sandy, surrounded by seagrass. On the coast of Kampung Baru Village, there are many marine biota, including crustaceans, gastropods, bivalves, echinoderms, sea cucumbers, starfish and others. Sea urchins are one of the most important biota because people in Kampung Baru Village use their gonads for daily consumption. The existence of sea urchins in coral reef ecosystems has a significant effect on the ecological balance. The purpose of this study was to determine the community structure of sea urchins in the coastal areas of Kampung Baru, Central Maluku Regency. It is necessary to do so so that the presence of sea urchins can be known so that the balance is well monitored. The method used is a quadratic linear transect. The results showed that the diversity of sea urchin species on the coast of the village of Kampung Baru, Banda Island, Central Maluku was 0.815, including the low category. The value of dominance is 0.512, which means there is a tendency for species to dominate. The density value is 0.065 and the distribution value is 0.277 which is included in the uniform category. Keywords: Community Structure, Sea Urchins, Kampung Baru, Banda Island